Construction of an Integration-Proficient Vector Based on the Site-Specific Recombination Mechanism of Enterococcal Temperate Phage φFC1 - Yang, Hee-Youn (American Society for Microbiology, 2002)
The genome of temperate phage φFC1 integrates into the chromosome of Enterococcus faecalis KBL 703 via site-specific recombination. In this study, an integration vector containing the attP site and putative integrase gene mj1 of phage φFC1 was constructed. A 2,744-bp fragment which included the attP site and mj1 was inserted into a pUC19 derivative containing the cat gene to construct pEMJ1-1. E. faecalis KBL 707, which does not contain the bacteriophage but which has a putative attB site within its genome, could be transformed by pEMJ1-1. Southern hybridization, PCR amplification, and DNA sequencing revealed that pEMJ1-1 was integrated specifically at the putative attB site within the E. faecalis KBL 707 chromosome. This observation suggested that the 2,744-bp fragment carrying mj1 and the attP site of phage φFC1 was sufficient for site-specific recombination and that pEMJ1-1 could be used as a site-specific integration vector. The transformation efficiency of pEMJ1-1 was as high as 6 × 10(3) transformants/μg of DNA. In addition, a vector (pATTB1) containing the 290-bp attB region was constructed. pATTB1 was transformed into Escherichia coli containing a derivative of the pET14b vector carrying attP and mj1. This resulted in the formation of chimeric plasmids by site-specific recombination between the cloned attB and attP sequences. The results indicate that the integration vector system based on the site-specific recombination mechanism of phage φFC1 can be used for genetic engineering in E. faecalis and in other hosts.